Synthesis, Characterization, Spectral and Antimicrobial Studies of Some Trivalent Ln(III) Metal Complexes with Ligands Containing ‘N’ and ‘O’ Donor Atoms - Kumar Mishra, Rajesh; Thakur, B.G. (Asian Journal of Chemistry, 2015)
Ten new coloured solid complexes of type [ML2X2], Where M=La(III), Pr(III), Nd(III), Sm(III) & Dy(III), ‘L’ = Ligand i.e., N-(3-methyl-thiocarbamyl-5-oxo-2-pyrazolin-4-ylene-N'-(4'-antipyrine)hydrazine (HATP) and N-(3-methyl-1-thiocarbamyl-5-oxo-2-pyrazolin-4-ylene)-N'-(4'-benzothiazole)hydrazine (HBTP) and ‘X’=H2O have been synthesized and characterized by their elemental analysis, molar conductance values, magnetic susceptibilities, UV, IR and NMR spectral studies. Elemental analysis confirms 1:2 stoichiometry of the synthesized complexes. Spectral studies confirms that the ligand ‘HATP’ and ‘HBTP’ acts as tetradentate and tridentate, respectively and coordinates to central metal ion by ‘N’ and ‘O’ donor atoms. Complexes are ten and eight coordinated. Further the ligands and synthesized complexes have been screened for their antibacterial activity against some Gram-positive and Gram-negative bacteria.